Dark of the moon - Sandford, John (Pocket Books, 2008)
In the small prairie town of Bluestem, a house explodes into flame, its elderly owner trapped inside, burned to a crisp on a makeshift funeral pyre. With a history involving financial scams and deviant activities with other men's wives, Flowers discovers that the victim wasn't the most popular guy in town. But that's not the reason Flowers is in Bluestem. Three weeks before, there was another murder - a doctor and his wife, the doctor found propped up in his own backyard, both eyes shot out. There hasn't been a murder in Bluestem in years, and now suddenly three? Flowers knows two things: this isn't a coincidence; this has to be personal. But jus how personal Flowers might not find out until too late. Because the next victim...could be him.